Children's Judgments About Prosocial Decisions and Emotions: Gender of the Helper and Recipient Matters. Issue 5 (11th March 2014) - Weller, Drika; Lagattuta, Kristin Hansen
<x xml:space="preserve">Abstract</x> Children ages 5–13 years (N = 82) responded to prosocial and prohibitive moral dilemmas featuring characters whose desires conflicted with another person's need for help or ownership rights. The gender of the characters matched for half the trials (in‐group version) and mismatched for the other half (out‐group version). Both boys and girls judged that people would more likely help and not harm the gender in‐group versus out‐group. Only girls exhibited gender bias in emotion attributions, expecting girls to feel happier helping girls and better ignoring the needs of boys. With increasing age, children exhibited greater awareness of the emotional benefits of prosocial sacrifice and made stronger distinctions by need level when evaluating prosocial decisions, obligations, and permissibility.